1997
DOI: 10.1103/physrevlett.78.1984
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Plateaus in Spin Chains: “Haldane Gap” for Half-Integer Spins

Abstract: We discuss zero-temperature quantum spin chains in a uniform magnetic field, with axial symmetry. For integer or half-integer spin, S, the magnetization curve can have plateaus and we argue that the magnetization per site m is topologically quantized as n͑S 2 m͒ integer at the plateaus, where n is the period of the ground state. We also discuss conditions for the presence of the plateau at those quantized values. For S 3͞2 and m 1͞2, we study several models and find two distinct types of massive phases at the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
698
6
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 720 publications
(774 citation statements)
references
References 28 publications
69
698
6
1
Order By: Relevance
“…A further possibility for a plateau in the value of Ω with increasing B is worth mentioning [44], as analogs are realized in SrCu 2 (BO 3 ) 2 [45] and NH 4 CuCl 3 [46]. So far we have found plateaus at Ω = 0 for B < ∆, and at Ω = 1/2 for large B.…”
Section: Strong Fieldsmentioning
confidence: 56%
“…A further possibility for a plateau in the value of Ω with increasing B is worth mentioning [44], as analogs are realized in SrCu 2 (BO 3 ) 2 [45] and NH 4 CuCl 3 [46]. So far we have found plateaus at Ω = 0 for B < ∆, and at Ω = 1/2 for large B.…”
Section: Strong Fieldsmentioning
confidence: 56%
“…32 An in-plane magnetic structure with Q = (0 2π/3) was theoretically predicted from the quantization condition of the plateau magnetization. 32 According to theoretical work by Oshikawa et al 53 for a Heisenberg spin system, the quantization condition on the magnetization at a plateau is p(S-m) = integer, where p and m are the period of the spin state and the magnetization per site, respectively. For the present compound with S = 1/2 Cu 2+ ions, the minimal necessary condition of the 1/3 plateau (m = 1/6) gives the period as p = 3.…”
Section: Resultsmentioning
confidence: 99%
“…About eight years ago Affleck and Oshikawa [18] demonstrated that such sum rules have a more general existence. By using a modification of the Leib Mattis theorem, Affleck and Oshikawa showed that the "large Fermi surface" which counts both local moments and conduction electrons develops in the one dimensional S = 1/2 Kondo model, even though in this case, the ground-state is not a Fermi liquid.…”
Section: Introductionmentioning
confidence: 99%